(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Nysius graminicola (Kaltenbach) and N. cymoides (Spinola) frequently cause serious damage to a range of summer vegetable and fruit crops, particulary sorghum, grape, tomato, peach. Their pest status is largely due to their capacity to colonize rapidly and attack crops en masse in the warmer months. These summer crops probably offer an extension to the normal range of temporary native habitats, when their natural forage plants suffer either because of adverse environmental conditions, or are eliminated by unaware management of the farmers. Their biology was investigated in Sicily from June to October during the past two years, on the spontaneous plants Pulicaria dysenterica (L.) Bemh., Conyza bonariensis (L.) Cronq., Aster squamatus (Sprengel) Hieron., Senecio lycopifolius Desf., Inula viscosa (L.) Aiton. The female of the up mentioned bugs egg-lay both on the flowers and seeds. All the postembryonal stages develop externally on flower heads, attacking their relative receptacles. From July 15th to until end of October each species performed not less than 3 generations, each lasted 35-42 days. The eggs (n=986) of both ligaeids were parasitized by Robertella dessarti Mineo (Scelionidae), for an average of 55.17%. With regard to the species of plants such a parasitization was 54.16% on A. squamatus, 30.82 on C. bonariensis, 70.00% on I. viscosa, 58.39% on P. dysenterica and 47.46% on S. lycopifolius.